Law Enforcement of Skimming as a Cyber Crime: Digital Forensic Challenges and Evidence in Court - Wardani, Dian Eka Kusuma; Raodiah; Gazali, Indrahayu M. Umar (Faculty of Law, Universitas Pekalongan, 2025)
Skimming is a form of cybercrime that continues to grow with the increasing use of digital banking technology. This method involves stealing customer card data through special devices installed on ATMs or payment terminals, resulting in significant financial losses. This article discusses law enforcement against skimming, focusing on two main aspects: digital forensic challenges and evidence in court. The research method used is a juridical-normative approach with a literature review, which includes analysis of laws and regulations, legal literature, and actual cases related to skimming. Furthermore, a case study approach is used to examine the application of digital evidence in the judicial process. The results show that investigators face difficulties in identifying electronic traces, analyzing evidence, and ensuring the authenticity of digital data that is vulnerable to manipulation. Another challenge lies in providing evidence in court, where judges and law enforcement officials often have limited technical understanding of digital forensics. However, judicial practice shows that digital evidence is admissible if obtained legally and supported by adequate forensic expertise. Thus, law enforcement against skimming requires synergy between regulations, technology, and the competence of law enforcement officials. Collaboration between digital forensic experts and law enforcement is key in addressing skimming as a cybercrime.